Studi Teoritis Pembentukan Momen Magnetik pada Alloy half-Heusler Mn2Ge - Anugrah Azhar; Muhammad Aziz Majidi (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2019)
Heusler alloy is a subclass material that consists of transition metal compounds with fascinating magnetic properties due to their magnetic moment value that is still studied by many researchers due to their magnetic moment value that can be predicted using a simple calculation called Slater-Pauling rule (SP rule)s. According to the SP rule, when the total number of the valance electron gives a value of 18 (for half-Heusler alloy), the magnetic momen of this material is predicted by the value of 0 μB. By using this simple calculation, one can make material that have zero magnetic moment value. On the other hand, those this materials generally hasve halfhalf-metallic behavior in which the spin orientation only occurs on the one direction of either in the majority or minority spin channel. Starting from those issues, we propose a theoretical study to investigate the magnetic moment formation of halfhalf-Heusler alloyalloy Mn2Ge. Our results show that Mn2Ge have magnetic moment of 0.03 μB and show the halfhalf-metallic feature of Mn2Ge.